Efeito local da metformina gel 1% como adjuvante no tratamento periodontal de pacientes portadores de diabetes mellitus tipo II com periodontite. Estudo clínico randomizado duplo-cego. - Ferreira, Bruna Fonseca (2023)
Effective periodontal therapy can help improve blood glucose levels in patients with diabetes mellitus (DM), yet there is no consensus on which periodontal treatment is the most suitable for diabetic patients. Metformin (MF) in periodontal therapy has shown benefits in reducing probing depth and gaining clinical attachment level. The aim of this study was to evaluate the efficacy of 1% metformin gel administered locally as an adjunct to basic periodontal treatment in patients with periodontitis in different states with type II diabetes mellitus, who were using oral metformin. This is a randomized, parallel, double-blind, clinical and laboratory-based clinical study. A total of 39 patients were evaluated, divided into two groups, CM (n=20): Periodontal therapy with an association of 1% metformin gel and SM (n=19): Periodontal therapy with an association of placebo gel. The patients were evaluated at 0, 3 and 6 months, through the following exams: clinical exams (clinical probing depth, bleeding on probing, clinical attachment loss and plaque index), hematological exams (fasting glucose, glycosylated hemoglobin, creatinine and total cholesterol and fractions) and collection of gingival crevicular fluid for evaluation of IL-17 by means of the ELISA test and to determine the amount of fluid absorbed (mm2). All data were statistically analyzed using the statistical program Bioestat@. Quantitative variables were evaluated regarding the assumption of normality (Shapiro-Wilk test). In cases where the assumption was in agreement, the ANOVA test was applied and later the Tukey test. In cases where the data were found to be in a non-normal distribution, the comparison was applied using the non parametric Kruskall-Wallis test followed by Dun's post-test, to compare the means in periods of 0, 3 and 6 months. In all tests, a significance level of 5% was adopted. Both groups significantly reduced the amount of plaque, bleeding on probing and the amount of gingival crevicular fluid in mm2 (p<0.05) while clinical probing depth was significantly reduced (p<0.05) only in the CM group. When evaluating the different probing depths, pockets <5 and ≥ 5 mm reduced significantly (p<0.05) in the CM group, while in the SM group, only pockets <5 mm were significantly reduced. The results of the hematological exams did not show statistical difference in this period and the same occurred with the amount of IL-17 present in the gingival crevicular fluid. According to the results obtained in the present study, the local application of 1% metformin gel in patients with PD and type II DM was effective when associated with basic periodontal treatment on periodontal clinical parameters, compared to the placebo gel.